2015
DOI: 10.1103/physrevx.5.041018
|View full text |Cite
|
Sign up to set email alerts
|

Electron-DopedSr2IrO4: An Analogue of Hole-Doped Cuprate Superconductors Demonstrated by Scanning Tunneling Microscopy

Abstract: Sr 2 IrO 4 was predicted to be a high-temperature superconductor upon electron doping since it highly resembles the cuprates in crystal structure, electronic structure, and magnetic coupling constants. Here, we report a scanning tunneling microscopy/spectroscopy (STM/STS) study of Sr 2 IrO 4 with surface electron doping by depositing potassium (K) atoms. We find that as the electron doping increases, the system gradually evolves from an insulating state to a normal metallic state, via a pseudogaplike phase, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 25 publications
(60 reference statements)
10
118
0
Order By: Relevance
“…4(e) at x ¼ 0.1 for ε ¼ 60 meV, which shows the destruction of the FS sections around X as in the clean case with long-range d-PSCO. More remarkable is the emergence of the fullfledged Fermi arcs as the folded part of the FS is destroyed by the scattering due to spatially fluctuating pseudospin current, in good agreement with the observed Fermi arcs and d-wave-like pseudogaps by ARPES and STM in heavily surface-K-doped iridates [28][29][30]. Figure 4(f) is a spectral intensity plot of the FS when the disordered pseudospin currents fluctuate spatially around a nonzero mean of the d-PSCO with Δ d ¼ AE30 meV to account for averaging over two domains.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…4(e) at x ¼ 0.1 for ε ¼ 60 meV, which shows the destruction of the FS sections around X as in the clean case with long-range d-PSCO. More remarkable is the emergence of the fullfledged Fermi arcs as the folded part of the FS is destroyed by the scattering due to spatially fluctuating pseudospin current, in good agreement with the observed Fermi arcs and d-wave-like pseudogaps by ARPES and STM in heavily surface-K-doped iridates [28][29][30]. Figure 4(f) is a spectral intensity plot of the FS when the disordered pseudospin currents fluctuate spatially around a nonzero mean of the d-PSCO with Δ d ¼ AE30 meV to account for averaging over two domains.…”
supporting
confidence: 84%
“…We argue that the hidden order has an electronic origin and can be generated spontaneously by the intersite Coulomb interactions due to the large spatial extent of the iridium 5d orbitals, turning the metallic phase of the iridates into an electron-doped quasi-2D Dirac semimetal. These findings provide new insights and perspectives for understanding the possible emergence of a superconducting phase [29,30].…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…A recent angle resolved photoemission (ARPES) study found an anisotropic pseudogap in Sr 2−y La y IrO 4 [6]. ARPES [7] and STM [8] experiments on K-covered Sr 2 IrO 4 further reported evidence for a d-wave gap closing at 30-50 K. In addition * dirk.vandermarel@unige.ch a degeneracy splitting of the bands near (π,0) was found in ARPES experiments [6] and a hidden order parameter has been claimed based on observations with optical second harmonic generation [9]. These observations have lead to different mutually exclusive speculations as to the nature of this state of matter, in particular superconducting fluctuations [7] and a d-wave pseudospin-current ordered state [10].…”
Section: Introductionmentioning
confidence: 97%